1966
DOI: 10.1002/aja.1001180105
|View full text |Cite
|
Sign up to set email alerts
|

The ultrastructure of the gastric mucosa in normal and hypophysectomized rats

Abstract: The objectives of this study were to observe with the electron microscope ( a ) the epithelial cell types found in the neck and isthmus of the gastric fundic gland of the rat, and ( b ) the effects of hypuphysectomy on the gland. The following cell types were distinguished in the neck of the fundic gland of the rat: nondifferentiated cell, immature surface cell, mucous neck cell, and neck parietal cell. In the normal gland, these cell types resembled each other in the possession of a ground cytoplasm and nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0
2

Year Published

1967
1967
1985
1985

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(39 citation statements)
references
References 35 publications
3
34
0
2
Order By: Relevance
“…However, undifferentiated cells in the present as well as previous studies (CORPRON, 1966;KATA-OKA, 1970) are identified as such by merely ultrastructural criteria: the absence of specific secretory granules, among others. Truly undifferentiated or pluripotential stem cells are difficult to identify by their morphology, and the contribution of such cells to new cell formation in the physiological renewal may be small, since morphologically identified undifferentiated cells are extremely scarce (Fig.…”
Section: Discussionsupporting
confidence: 67%
“…However, undifferentiated cells in the present as well as previous studies (CORPRON, 1966;KATA-OKA, 1970) are identified as such by merely ultrastructural criteria: the absence of specific secretory granules, among others. Truly undifferentiated or pluripotential stem cells are difficult to identify by their morphology, and the contribution of such cells to new cell formation in the physiological renewal may be small, since morphologically identified undifferentiated cells are extremely scarce (Fig.…”
Section: Discussionsupporting
confidence: 67%
“…The results presented here indicate that the non-differentiated neck cell, which has been suggested to represent the origin of the different cells in the gastric gland (Corpron, 1966;Rubin et al 1968;Matsuyama & Suzuki, 1970), has the capacity of producing both prochymosin and pepsinogen during the differentiation phase. When the diet is changed, i.e.…”
Section: Rocket Immunoelectrophoresismentioning
confidence: 76%
“…The ratios of the enzymes in the present material are shown in Table 1. DISCUSSION The secretion of chymosin from the gastric mucosa is highly correlated with milk-feeding and age (Garnot et al 1977;Andren et al 1980Andren et al , 1981 Several workers (Corpron, 1966;Rubin, Ross, Sleisenger & Jeffries, 1968;Matsuyama & Suzuki, 1970) have suggested that the mucous neck cell is the precursor of the chief cell, and Kataoka (1970) observed groups ofimmature chiefcells in the upper part of the base in gastric glands of the mouse. If this is so, the following hypothesis might explain the lack ofprochymosin-containing chief cells in the lower base of older animals (see also Fig.…”
Section: Rocket Immunoelectrophoresismentioning
confidence: 99%
“…The ultimate purpose of our works is to establish cell lines from gastric mucosal cells, so that the interest was naturally focused on the separation of cells with growth potential, i.e. so-called immature, undifferentiated, indifferent and generative cells of the mucosa, which are called G-cells in this paper (Hunt and Hunt 1962;Corpron 1966;Johnson and Young 1968). Methods to obtain cell suspensions from the neck zone of the gastric mucosa of rats with high ratios of G-cells are reported and evaluated.…”
mentioning
confidence: 99%